2015
DOI: 10.1007/s11523-015-0382-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Single Nucleotide Polymorphisms in STAT3 with Hand-Foot Skin Reactions in Patients with Metastatic Renal Cell Carcinoma Treated with Multiple Tyrosine Kinase Inhibitors: A Retrospective Analysis in Japanese Patients

Abstract: The rs4796793 genotype appears to be a novel factor for mTKI-induced HFSR in patients with mRCC. Prospective translational trials with larger numbers of patients are required to confirm our results. This research suggests a potential benefit of STAT3 polymorphism screening in patients treated with mTKIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Results from our previous study indicated that sunitinib-induced HFSR is likely to develop within 6 weeks of sunitinib initiation [22]. In this study, HFSR evaluated at weeks 3 and 6 was considered induced by sunitinib.…”
Section: Discussionmentioning
confidence: 99%
“…Results from our previous study indicated that sunitinib-induced HFSR is likely to develop within 6 weeks of sunitinib initiation [22]. In this study, HFSR evaluated at weeks 3 and 6 was considered induced by sunitinib.…”
Section: Discussionmentioning
confidence: 99%
“…In recent works, sunitinib was reported to induce RCC cell apoptosis and to decrease immunosuppressive cell numbers as a result of STAT3 inhibition. 1,[24][25][26][27] STAT3 is activated by the stimulation of IL-6 and growth factors, and is then involved in the regulation of cellular differentiation, survival, and proliferation. 28,29) Immune systems such as Toll-like receptor signaling and B-cell receptor signaling and inflammatory cytokines relate to stomatitis development.…”
Section: Discussionmentioning
confidence: 99%
“…1) However, stomatitis is a very frequent complication associated with molecular-targeted drugs. Sunitinib, one of multiple tyrosine-kinase inhibitors currently used as first-line treatment for mRCC, is associated with stomatitis and has a reported incidence of 52% at any grades.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the initial clinical course of RCC is asymptomatic, resulting in 25–30% of patients presenting with metastatic disease when diagnosed [ 2 ]. Several molecular-targeted drugs have emerged as the first-line treatment for mRCC patients attributed to its insensitivity to chemotherapy and radiotherapy [ 3 6 ]. Sunitinib, as a small-molecule receptor tyrosine kinase inhibitor (TKI), gaining the approval of the Food and Drug Administration (FDA) in 2006.…”
Section: Introductionmentioning
confidence: 99%